The Use of Aviation in Oceanographic Research in the Arctic (Primenenie Aviatsii v Okeanograficheskikh Issledovaniya V Arktike) - Laktionov,A. F.; Shamontev,V. A. (1959)
Application of aircraft in ice reconnaissance, in setting up drifting research stations on ice, and in aiding polar navigation is reviewed, disclosing the progress, the trends and future prospects in mastering the Arctic Ocean. (Author) Trans. of Problemy Arktiki (USSR) n2 p19-31 1957, by M. Slessers. Also available as TT-61-13879.